“Teaching Template Quiz Maker" as Edutainment Software to Create Test as Material in Teaching English at Junior High School - Muslimah Muslimah; Havid Ardi (Journal of English Language Teaching, 2012)
The purposes of this paper are to explain the ways of the development of exercises or tests as a material at Junior High School by using Teaching Template Quiz Maker. Besides, this software can decrease students’ bored in understanding the material that is designed trough quiz. This software has some templates that can take students’ attention in doing exercise because they have kind of exercises and options of display. For example, color, sound, also it uses a computer as a media. Then, this software can increase students’ vocabulary also some skills such as speaking, reading and writing. The last, it can create fun learning which students-centered are appear during the learning process.   Abstrak Tujuan makalah ini adalah untuk memaparkan cara pengembangan latihan sebagai bahan pengajaran di Sekolah Menengah Pertama (SMP) dengan menggunakan Teaching Template Quiz Maker. Software ini dapat mengurangi kejenuhan siswa dalam memahami material melalui latihan yang di desain melalui kuis. Software ini memberi 9 jenis model kuis yang mampu menarik perhatian siswa dalam mengerjakan latihan karena mempunyai banyak model latihan dan banyak pilihan tampilan, seperti warna, suara, serta penggunaannya dengan menggunakan media komputer. Selain itu software ini dapat meningkatkan kosakata siswa serta meningkatkan kemampuan berbicara, membaca dan menulis. Kemudian, software ini dapat menciptakan suasana belajar di mana siswa dominan dalam proses belajar.